Collaborative Care Interventions for Depression in the Elderly: A Systematic Review of Randomized Controlled Trials. (1st February 2009) - Chang-Quan, Huang; Bi-Rong, Dong; Zhen-Chan, Lu; Yuan, Zhang; Yu-Sheng, Pu; Qing-Xiu, Liu
Abstract : Objective: To determine the effective components and the feasibility of collaborative care interventions (CCIs) in the treatment of depression in older patients. Methods: Systematic review of randomized controlled trials, in which CCIs were used to manage depression in patients aged 60 or older. Results: We identified 3 randomized controlled trials involving 3930 participants, 2757 of whom received CCIs and the others received usual care. Collaborative care interventions were more effective in improving depression symptoms than usual care during each follow-up period. Compared with baseline, thoughts of suicide in subjects receiving CCIs significantly decreased (odds Ratio [OR], 0.52; 95% confidence intervals [CI], 0.35−0.77), but not that in those receiving usual care (OR, 0.85; 95% CI, 0.50−1.43). Subjects receiving CCIs were significantly more likely to report depression treatment (including any antidepressant medication and psychotherapy) than those receiving usual care during each follow-up period. Collaborative care interventions significantly increased depression-free days, but did not significantly increase outpatient cost. At 6 and 12 months postintervention, compared with those receiving usual care, participants receiving CCIs had lower levels of depression symptoms and thoughts of suicide. Moreover, participants receiving CCIs were significantly more likely to report antidepressant medication treatment, but were not significantly more likely to report psychotherapy. Collaborative care interventions with communication between primary care providers and mental health providers were no more effective in improving depression symptoms than CCIs without such communication. Conclusions: Collaborative care interventions are more effective for depression in older people than usual care and are also of high value. Antidepressant medication is a definitely effective component of CCIs, but communication between primary care providers and mental health providers seems not to be an effective component of CCIs. The effect of psychotherapy in CCIs should be further explored.